2009
DOI: 10.1007/s12576-009-0045-7
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine profile and testicular histomorphometry in adult rat offspring of diabetic mothers

Abstract: This investigation was conducted to evaluate the effect of maternal diabetes on fetal testicular structure and function, and reproductive hormones levels. Sixteen female rats were divided into two groups. Diabetes was induced in one group by alloxan. Blood was collected from 90-day-old male offspring of both groups, and the level of blood glucose, testosterone, FSH and LH in their serum was measured. Weight, volume and various histological parameters of testes were determined. A significant increase in blood g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
3
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 22 publications
4
34
3
8
Order By: Relevance
“…It was observed that the therapies studied in this work succeeded in controlling the STZ-induced diabetic [24], pioglitazone [23] and sitagliptin [36,37]. Although the weights of testis, epididymis and seminal vesicle as well as testosterone hormone level was significantly reduced in the STZ-induced diabetic rats and these findings were consistent with those of previous studies [38][39][40][41], metformin succeeded to restore it back to values with insignificant difference compared to the NC group while the pioglitazone and sitagliptin failed to do that. Reduced serum testosterone in diabetic rats was attributed in previous studies to neuroendocrine dysfunction and the absence of the stimulatory effect of insulin on the LC [3,42].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was observed that the therapies studied in this work succeeded in controlling the STZ-induced diabetic [24], pioglitazone [23] and sitagliptin [36,37]. Although the weights of testis, epididymis and seminal vesicle as well as testosterone hormone level was significantly reduced in the STZ-induced diabetic rats and these findings were consistent with those of previous studies [38][39][40][41], metformin succeeded to restore it back to values with insignificant difference compared to the NC group while the pioglitazone and sitagliptin failed to do that. Reduced serum testosterone in diabetic rats was attributed in previous studies to neuroendocrine dysfunction and the absence of the stimulatory effect of insulin on the LC [3,42].…”
Section: Discussionsupporting
confidence: 91%
“…The disorganized germinal epithelium and edematous thickened interstitial connective tissue in the testis of diabetic rats have been described in the previous studies [33,40,[42][43][44] and have been also observed in this study. The crowded nuclei and cytoplasmic vacuoles of the epithelial lining the epididymis of the DC observed in this study was in agreement with those of Soudamani et al [45] who attributed them to shrinkage of epididymal tubules.…”
Section: Discussionsupporting
confidence: 86%
“…Sperm concentration and motility were both significantly lower in diabetic compared with control rats (Kim and Moley, 2008). Finally, a recent study on the offspring of diabetic mothers showed that the number of spermatogonia (226.3%) and the diameters of the seminiferous tubules (211%) were significantly lower compared with controls (Jelodar et al, 2009).…”
Section: Animal Studiesmentioning
confidence: 94%
“…В эксперименте на лабораторных животных показано, что ухудшение показателей репродуктивной системы отмечается у самцов, рожденных от матерей с СД: по сравнению с потом-ством от матерей без СД у них ниже уровень гонадотропных гор-монов и тестостерона крови, а в гонадах меньше на 15,6% клеток Лейдига и на 14,9% клеток Сертоли, количество сперматогоний снижено на 26,3%, а диаметр семенных канальцев -на 11% [40].…”
Section: экспериментальные данныеunclassified